Ketahanan Literasi Anak-Anak di Masa Pandemi melalui Aplikasi Let’s Read (Children's Literacy Resilience in a Pandemic Period Through the Let's Read Application) - Endang Sri Maruti (Indonesian Language Education and Literature, 2022)
This study aims to describe the improvement of children's digital literacy skills. Research data in the form of the results of children's reading activities with the application. Data were collected by questionnaires and from observations and strengthened by data from interviews with children. The collected data is then analyzed with reference to the flow model. The results showed that the use of the Let's Read application could improve digital literacy for the children of Kampung Wonopuro. Utilization of spare time can be filled by playing while learning to read. The language in the reading text that is read is not only Indonesian but can be regional or foreign languages.Penelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan literasi digital anak-anak. Data penelitian berupa hasil kegiatan membaca anak dengan aplikasi. Data dikumpulkan dengan angket dan dari observasi dan diperkuat dengan data dari wawancara dengan anak-anak. Data yang terkumpul kemudian dianalisis dengan mengacu pada model alir. Hasil penelitian menunjukkan bahwa pemanfaatan aplikasi Let’s Read dapat meningkatkan literasi digital bagi anak-anak Kampung Wonopuro. Pemanfaatan waktu senggang dapat diisi dengan bermain sambil belajar membaca. Bahasa dalam teks bacaan yang dibaca juga tidak hanya bahasa Indonesia, tetapi bisa bahasa daerah maupun bahasa asing.